PENGELOLAAN PEMBELAJARAN IPA DENGAN PENDEKATAN KONSTRUKTIVISME UNTUK MENANGGULANGI MISKONSEPSI DI SD KEPAHIANG - Bambang Stiawan (Manajer Pendididikan, 2016)
This research aims to tackle the misconceptions in identifying some typical types of relationships (symbiosis) and the relationship between eating and being eaten alive beings (foodchain) in learning management of natural science. This research uses a Classroom Action Research. The subjects of this research are studens of fourth grade. The technique of collectingdata is through observation. The data are analyzed with descriptive percentage technique. The results show that with the adoption learning management by constructivist approach can tacklingthe students misconception.Keywords: misconceptions, management, constructivism